Problematic of languages within educative systems in Africa (Foro de Educacion, 2012)
Our observation contains three parts: preamble, some key questions and a conclusion. It summarizes colonial period and postcolonial by taking Democratic Republic of Congo as starting point. In this country, the colonizer had recourse to local languages in elementary teaching and to French afterwarlds. This system continued somehow in the postcolonial period. Somehow because reality on the ground doesn’t correspond always to the verb.Among key questions which can be examined, we can cite the choice carried on the metropolitan language, recousing to local languages, form of language to be taught, the method to guide the drafting of books and useful tools for a good linguistic policy within educative sector. That is shown in conclusion by indicating the positive and the negative coming from recourse to such or such language as vehicle of teaching.